2018
DOI: 10.1007/s11684-018-0628-x
|View full text |Cite
|
Sign up to set email alerts
|

Dental stem cell and dental tissue regeneration

Abstract: The teeth are highly differentiated chewing organs formed by the development of tooth germ tissue located in the jaw and consist of the enamel, dentin, cementum, pulp, and periodontal tissue. Moreover, the teeth have a complicated regulatory mechanism, special histologic origin, diverse structure, and important function in mastication, articulation, and aesthetics. These characteristics, to a certain extent, greatly complicate the research in tooth regeneration. Recently, new ideas for tooth and tissue regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 54 publications
1
103
0
Order By: Relevance
“…28,29 Stem cells from apical papilla showed significantly high mineralization and proliferation. 30,31 Even in an immature tooth with pulp necrosis and AP, human apical papilla retained SCAP vitality. 32 Therefore, we selected hSCAPs to probe into the mechanism of root repair.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Stem cells from apical papilla showed significantly high mineralization and proliferation. 30,31 Even in an immature tooth with pulp necrosis and AP, human apical papilla retained SCAP vitality. 32 Therefore, we selected hSCAPs to probe into the mechanism of root repair.…”
Section: Discussionmentioning
confidence: 99%
“…Stem/progenitor cells derived from oral cavity express several mesenchymal markers including CD29, CD73, CD90, and CD105 as well as embryonic markers such as Sox2, Nanog and Oct4 and can differentiate into multiple cell lineages [11,13,[30][31][32][33]. Importantly, some dental stem cells exhibit more embryonic-like features than bone marrow stem cells and umbilical cord [31][32][33][34]. Therefore, mesenchymal stem cells derived from the oral cavity are believed to be very important and valuable resource for eventual development of cells for clinical/therapeutic applications not only in dentistry but also in medicine.…”
Section: Dental Stem Cellsmentioning
confidence: 99%
“…Furthermore, dental stem cells are convenient to obtain, possess low immunogenicity and free of any ethical controversy, which might be good resource for tissue regeneration. 67,68 Seeding dental stem cells on appropriate biomaterials may promote their capability for bone, cartilage or dental tissue regeneration. Hu et al 69 have transplanted human DPSCs (hDPSCs) into a swine model for periodontal regeneration, and the results showed that translating hDPSCs into this large animal model could significantly improve periodontal bone regeneration and soft tissue healing.…”
Section: Dna Nanostructures Have Applications In a Wide Array Of Fielmentioning
confidence: 99%